Islamic state, Islamic economy, and siyasah syar’iyah: An Islamic political-economy approach - Putriani, Diyah; Kayadibi, Saim; Nursyamsiah, Tita (2012)

(untitled)
This research paper is intentionally designed to build a framework of Islamic economy into one picture of Islamic state concept. The research paper employ quantitative and historical approach. The result of geometric mean computation showing the growth of money supply in Iceland is higher than the growth of real GDP and the the inflation rate reaches 18.91 percent. The regression analysis is carried-out based on natural logarithm (Ln) model. The estimated coefficient of M1 in Iceland is much higher than the estimated coefficient of GDP. This result also supports the finding of geometric computation. In other words, there is an economic problem in Iceland created by the working of compounded fiat-money interest rate. It has implicitly proven that since the power of Islamic government is absent in this world, then the Islamic state will never be established. Therefore, the need of siyasah shar’iah to build Islamic government before establish Islamic state becomes an obligatory. Keywords: Islamic Economy; Islamic State; Islamic Welfare; Siyasah Shari‘ah; Maqasid al-Shari‘ah.